2013
DOI: 10.3109/21681805.2013.829519
|View full text |Cite
|
Sign up to set email alerts
|

How significant is upgrade in Gleason score between prostate biopsy and radical prostatectomy pathology while discussing less invasive treatment options?

Abstract: Upgrade in biopsy GS is a predictor for aggressive tumours with a higher risk for biochemical recurrence than concordant tumours. It may be observed in about a quarter of patients. As it was not possible to identify correctly those patients who may experience an upgrade in GS, patients who are candidates for less invasive treatment options must be informed about the risk of upgrading and the possibility of a worse clinical course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 23 publications
(38 reference statements)
0
10
1
1
Order By: Relevance
“…Regarding upgrade in Gleason score, Suer et al [12] found that an upgrade in Gleason score between biopsy and radical prostatectomy specimen occurred in 29% of cases compared to our results of 48% (47/98). Furthermore, another retrospective study found that overall 35% of the patients had an upgraded Gleason score after radical prostatectomy [13].…”
Section: Discussioncontrasting
confidence: 86%
“…Regarding upgrade in Gleason score, Suer et al [12] found that an upgrade in Gleason score between biopsy and radical prostatectomy specimen occurred in 29% of cases compared to our results of 48% (47/98). Furthermore, another retrospective study found that overall 35% of the patients had an upgraded Gleason score after radical prostatectomy [13].…”
Section: Discussioncontrasting
confidence: 86%
“…This may explain, in part, the difference in upgrading rates in 3+3 vs. 3+4 disease. Poor concordance rates have been described in the prostate cancer literature 11,26 and the lack of a central pathologic review in SEER data is a limit to this discussion. We also were unable to evaluate prostate gland volume, PSA density, the percent of core involvement, or the length of cores taken, all of which have been described as prognostic and may have added further clarification to this analysis.…”
Section: Discussionmentioning
confidence: 94%
“…4 These limitations are further suggested by the significant number of patients (25-60%) upgraded at the time of radical prostatectomy (RP). [5][6][7][8][9][10][11][12][13] Therefore, an improved understanding of the clinical factors associated with occult aggressive disease is needed to better inform treatment recommendations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fakat diğer faktörlerin de önemini koruduğunu söyleyebiliriz. GS'de yükselme gözlenen hastalarda biyokimyasal nüks oranının yüksek olması nedeniyle GS'deki artışı öngören tüm faktörlerin tam anlamıyla aydınlatılması önem arz etmektedir (26,27). Ayrıca PİB GS'yi değerlendiren patoloğun da belli bir tecrübeyle dikkatli değerlendirmesinin önemli etkenlerden biri olduğu belirtilmektedir, bu bakış açısı ile yapılan bir araştırmada üropatolog tarafınca değerlendirilen hastalardaki derece yükselmesinin diğer gruba göre daha düşük oranda saptandığı vurgulanmaktadır (28).…”
Section: Discussionunclassified